Aplikasi Business to Business Marketplace Jasa Pariwisata Menggunakan Kotlin - Ratni Ratni Asih; I Wayan Dharmana; Ricky Aurelius Nurtanto Diaz (Media Aplikom, 2019)
Tourism industry has the business process of tourism service transaction between merchant and agent. That business process between merchant and agent is known as business-to-business (B2B). Merchant has role as inventory providers and agent as sellers. Based on the information, the transaction between the merchant and agent is still done conventionally. The merchant has to find the potential agent that ready to sell their products, negotiate special rate and the term of payment. Long negotiation process makes the marketing coverage become less. On the agent side, the sales potential isn’t maximal because the limitation of product that they can sell. Based on the explanation above, it is necessary to build an app as solution with concept of business to business tourism service marketplace. Android mobile application was developed to fulfill the merchant and agent necessary in mobility. Application was developed with features such as inventory management, stock management, transaction, booking management, and fund management (topup, withdraw and payment history). The transaction done by the agent will be paid by using active balance that can be added by bank transfer to virtual account. Kotlin was used by the writer to develop the application and black box testing method for testing